The analysis of orofacial esthetic proportions with natural maxillary anterior teeth and perception of smile attractiveness in Pakistani citizens: a 2D photographic and 3D digital dental models study - Ahmed, Naseer (2022)
This study aimed to analyse faciodental proportion and perception of an attractive smile in Pakistani citizens. Phase one consisted of 230 and phase two 286 participants. The photographs of the full face and teeth were captured in a retracted smile, followed by maxillary impression and cast construction. The cast was then converted to 3D models. In phase two the photoshoped dental pictures were used to collect responses from dentists and laypersons about a particular smile. The data were analyzed by SPSS-25. The classic theories of golden proportion, golden percentage, Preston proportion, and recurring esthetic dental proportion proposed for North American population were not found in Pakistani citizens. The study proposed a ratio of 77% for lateral and central incisors and 107% for canine and lateral incisor teeth. The inner-intercanthal distance modified by golden percentage value of 25% was similar to combined central incisor width. The modified bizygomatic distance was larger than anterior teeth width. The interpupillary distance modified by golden proportion 62% was found to be consistent with intercanine distance in female participants. The facial proportions modified with 70% RED proportion showed a significant difference with anterior teeth width. The width of maxillary anterior teeth measured on plaster and 3D dental cast showed no significant difference. The interpupillary distance, inner-intercanthal distance, and bizygomatic distance could not be directly used to predict combined central incisors width and intercanine distance. The inner-intercanthal distance modified by golden percentage and interpupillary distance by golden proportion can be used to predict maxillary anterior teeth width. Additionally, interphiltral distance modified with Preston proportion is a reliable metric to predict combined central incisor width. A significant difference in gender disparity was found when facial proportions were modified with dental proportions except in the case of inner-intercanthal and interphiltral distance modified by golden percentage and Preston proportion respectively. The 70% recurrent esthetic dental proportion was not a reliable method to predict maxillary anterior teeth width. The phase two of study describes that; the dentist and layperson preferred a RED proportion-based smile, the most attractive. The dominant tooth in smile was selected to be central incisor by participants of this study. Teeth arrangement and color was selected as primary factor for deciding the preferred proportional view by most dentists and layperson.